La caduta degli dèi filosofi. Incontro con Giacomo Marramao e Massimo Fagioli - Fagioli, Massimo; Marramao, Giacomo (Il sogno della farfalla, 2007)
The meeting between the philosopher Giacomo Marramao and the psychiatrist Massimo Fagioli, held on 11.3.2007 at the Amore and Psiche bookshop in Rome was organized by Elisabetta Amalfitano and Simona Maggiorelli responsible for having interviewed Marramao who has proposed a critical reading of some of the untouchable masters of the Italian left among which Foucault and Heidegger. Starting off from this theme the psychiatrist and the philosopher, each from his own viewpoint, debated these issues as well as taking questions from the floor in a broad discussion that crossed many themes all connected in some way to a research into the human identity: the dialectic between creativity and technology; the relationship between dream and experience, between images and language, the unconscious and art; birth as the beginning of human life and of a temporal dimension; the critique of the philosophy of Nietszche and Heidegger; the Übermensch, the death instinct, the concept of being as an annulment of the other and the cultural foundations of Nazism; the lack of a scission between one’s life and one’s thinking; the proposition of an sane irrationality and the possibility of a cure for mental illnesses; the distinction between negation and lies; sexuality, the relationship between a human that differs from oneself, the general acceptance of diversity and a critique of the “identity obsession”; the cultural aspects of globalization; the importance of research into human reality as a definition of the identity of the left wing.